Calculation of Atomic Scattering Factor For X-ray in Copper - Muhsin Hasan Ali (Tikrit Journal of Pure Science, 2023)
In this paper the atomic scattering factor f(  has been calculated for x-ray in copper using Wave function involves The independent particle approximation for the values , The physical importance of this factor appears in its relation with the several important atomic properties such as, the coherent scattering intensities, the total scattering, the incoherent scattering function, the cross section for coherent, incoherent scattering, the differential of electrons scattering from atom and the geometrical structure factor. There was difference of 23% between the values has been found and the values has been measured for atomic scattering factor.